PENGARUH KETIMPANGAN DISTRIBUSI PENDAPATAN DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI PROVINSI JAWA TENGAH PERIODE 2017-2021 - Neneng Oktaviani; Syakira Putri Rengganis; Deris Desmawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The current problems of income inequality, slow economic growth, and other interrelated complexities are all directly linked to poverty. Finally, all nations must fight poverty in order to provide a recognized and prosperous life for their citizens. Therefore, the aim of this study is to ascertain how poverty will change in Central Java Province between 2017 and 2021 as a result of inequality in income distribution and economic growth. Using quantitative research techniques, this research. Inequality of Income Distribution, Economic Growth, and Poverty The Central Statistics Agency (BPS) of Central Java Province in 2017–2021 is a secondary data source with time series data. In addition, other methods were used to collect and analyze the data. and processed using SPSS 25.0 software. The results of this study indicate that the partial and simultaneous test results show that the Inequality of Income Distribution and Economic Growth does not have an insignificant effect on the Poverty Level. But secondly, when the correlation and determination tests were carried out, the results showed that the two independent variables had a relationship of 64.1% and an influence of 41.1% on the Poverty Level in Central Java Province for the 2017-2021 period.